Finance and climate change risk: Managing expectations - Claudio Borio; Stijn Claessens; Nikola A. Tarashev (EconPol Forum, 2023)
The financial sector has a key role to play in supporting the green transition. It is unrealistic to expect financial markets to induce the green transition unless the right signals come from the real economy. Unrealistic expectations can set the financial sector up for failure and derail the green transition. Risks to financial stability stem from exposure to overvalued emission-intensive assets, but also to overvalued "green" assets or assets that purport to be green
Keywords: 330